PROJECT MANAGEMENT FOCUSED ON STAKEHOLDER MANAGEMENT IN PERTAMINA’S BOYOLALI–PENGAPON PIPELINE PROJECT - Iwan Setiawan; Gatot Yudoko (RADJA PUBLIKA, 2026)
The Boyolali–Pengapon pipeline project is a national‐priority infrastructure initiative by PT Pertamina Patra Niaga. The project that seeks to improve Central Java’s fuel distribution faces stakeholder challenges that are intricate. From securing government approval, acquiring land, and managing relationship with the local communities, an effective stakeholder engagement framework is crucial to ensure the project stays on its schedule and budget. In accordance to that, this study analyzes the application of Pertamina’s stakeholder engagement in the Boyolali-Pengapon pipeline project. Data were gathered through semi-structured interviews with Pertamina project managers, government regulators, local community representatives, and the pipeline’s engineering partner, supplemented by analysis of project documents and reports. Thematic analysis was conducted using stakeholder mapping tools (the Stakeholder Salience Model and Power–Interest Grid) in line with PMI’s stakeholder engagement processes. The study’s objectives are to identify the project’s key stakeholders and their interests, assess the engagement practices used, document stakeholder-related issues, and evaluate how the stakeholder management approach affected the project’s schedule, cost, and community acceptance. The research finds suggest managing stakeholder proactively benefited the project result significant. Major delays were prevented through early engagement. Challenges of land acquisition and permit were also present, yet were not a hindrance for the project as they were addressed through negotiation and collaboration with local authorities. Consequently, the disruption avoided from legal disputes that might be costly and the small investments made in engagement helps the project to stay on budget. All in all, the case shows that large infrastucture projects needs a formal stakeholder engagement process to schedule compliance, keep cost controlled, and gain support from the local community.